If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3t = 3 + 4s Solving 2 + 3t = 3 + 4s Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3t = 3 + -2 + 4s Combine like terms: 2 + -2 = 0 0 + 3t = 3 + -2 + 4s 3t = 3 + -2 + 4s Combine like terms: 3 + -2 = 1 3t = 1 + 4s Divide each side by '3'. t = 0.3333333333 + 1.333333333s Simplifying t = 0.3333333333 + 1.333333333s
| 6(2-x)-(3-x)=7(2x+3) | | 3x^2+57=0 | | a+2(a+3)=9 | | 17=4p-3 | | H=-16t^2+32+5 | | 1000*.01*5= | | 18=4y+2y | | 4x=x^2+42 | | 2x^2+57=0 | | 9/11-5/11= | | 136*5= | | 1700*.08= | | -7/16x1/7 | | 2x+5,1=3(x-4,2) | | 0=0-5x | | 4x^2-1/x=0 | | 5x=(-1/5) | | 6x+9+2x+8=25 | | 2(x-3)+48x+5=6 | | 0.5x-4= | | 9=5-2x | | 4x+6x+20=90 | | A-23=3+a | | 5y+8x-2y+12x= | | (-3)=x^2-16 | | X^2-2t-35=0 | | p-14=39 | | 29=4n-6+n | | .20x+1.5=.25x+.75 | | (2x)x-3=16 | | 8k+35k= | | 9=6+3t |